Exploring Research on Computational Thinking in Mathematics: Trends, Challenges, and Impact on Modern Learning - Aulia, Mirza; Fatimah, Siti; Dahlan, Jarnawi Afgani; A, Abdul Wahab (FKIP Universitas Lampung, 2025)
Computational Thinking (CT) has been recognized as one of the essential skills of the 21st century and is increasingly being integrated into educational curricula in various countries. This study aims to analyze trends, challenges, and the impact of CT in mathematics education through a Systematic Literature Review (SLR) approach of 41 selected articles from the Scopus database covering the period from 2019 to 2024. The analysis results show a significant increase in the number of publications related to CT in mathematics education, with the highest peak occurring in 2023. Scratch technology was identified as one of the most commonly used tools to support CT learning, although there was considerable variation in the types of technology used in the reviewed literature. The most frequently studied mathematics topics were geometry and number patterns, while topics such as trigonometry and measurement were still rarely explored. The findings also indicate that CT has a positive impact on the mathematics learning process, which can be grouped into three main areas: (1) CT's contribution to students' understanding and learning outcomes, (2) the role of digital technology in supporting the implementation of CT, and (3) the relationship between CT and the development of higher-order mathematical thinking skills. However, six categories of challenges in implementing CT in the classroom were also identified, including: (1) barriers to using technology for CT learning, (2) lack of training and guidance for teachers, and (3) limitations in infrastructure and supporting facilities. To address these challenges and optimize the potential of CT in transforming mathematics learning, close collaboration between researchers, educators, and policymakers is required. Keywords: computational thinking, systematic literature review, mathematics learning.